2001
DOI: 10.1007/s001980170094
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease After Liver Transplantation: A Long-Term Prospective Study of Bone Mass Changes, Hormonal Status and Histomorphometric Characteristics

Abstract: After liver transplantation there is a high incidence of fractures, with important rates of bone loss during the first months. However, the long-term evolution of bone mass and metabolism parameters have been scarcely studied. In order to determine the incidence and risk factors involved in the development of skeletal fractures and to analyze the long-term evolution of bone mass, bone turnover and hormonal status after liver transplantation, a 3-year prospective study was performed in 45 patients following liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
119
2
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 27 publications
(55 reference statements)
11
119
2
9
Order By: Relevance
“…It has been demonstrated that the bone health before transplantation may be a predictive factor of bone loss and fracture after the liver is transplanted (38). In fact, prospective studies show that the risk of post-transplantation bone loss and fractures were related to age, pre-transplantation BMD and previous vertebral fracture as well as menopause status (39,40). Bone turnover has been reported to be low in many patients with liver failure; however, there is conversion to a high turnover state after liver transplantation that persists afterward.…”
Section: Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the bone health before transplantation may be a predictive factor of bone loss and fracture after the liver is transplanted (38). In fact, prospective studies show that the risk of post-transplantation bone loss and fractures were related to age, pre-transplantation BMD and previous vertebral fracture as well as menopause status (39,40). Bone turnover has been reported to be low in many patients with liver failure; however, there is conversion to a high turnover state after liver transplantation that persists afterward.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…The progression of bone loss seen after liver transplantation is similar to that following lung and cardiac transplantation, being more severe in the first 6 months. One bone histomorphometry study showed that bone loss stops around 6 month, followed by a gain of bone mass, mainly at cancellous bone, in the first 2 years after the liver transplantation (39). This increase in BMD is significant higher among premenopausal than perimenopausal and postmenopausal women, probably due the protective estrogen effect to the skeleton (40).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Most of these fractures occurred in the spine; however, since in some of these studies spinal X-rays were not routinely performed, the true number of vertebral fractures is likely to have been underestimated. In some studies, however, lower fracture rates have been reported.…”
Section: Incidence Of Fragility Fractures After Transplantationmentioning
confidence: 99%
“…7,8,15,17,[20][21][22][23][24][25] Bone loss affects the spine and the proximal femur, some studies suggesting greater bone loss at the latter site. 17,18,26 The majority of studies indicate that there is at least some recovery of bone mineral density after the first year or so of transplantation, although this finding has not been universal.…”
Section: Changes In Bone Mineral Density After Liver Transplantationmentioning
confidence: 99%
“…In the first 6 months after OLT, bone mineral density (BMD) significantly declines, and this decline often is accelerated by immunosuppressive medications, corticosteroids, and immobility. [3][4][5][6] After 6 months, BMD increases rapidly and, by 12 months, approaches pre-OLT values. 6 However, some patients continue to lose BMD greater than 24 months after OLT and are at risk for osteoporotic fractures.…”
mentioning
confidence: 99%